2021
DOI: 10.1186/s40792-021-01189-5
|View full text |Cite
|
Sign up to set email alerts
|

INI1-negative colorectal undifferentiated carcinoma with rhabdoid features and postoperative rapidly growing liver metastases: a case report and review of the literature

Abstract: Background Malignant tumors with rhabdoid features are extremely rare. They can occur in various organs, including the gastrointestinal tract, with common clinical features of high malignancy and poor prognosis. Case presentation A 41-year-old man visited our hospital complaining of lower abdominal pain and fever. Computed tomography (CT) revealed two wall-thickening lesions in the rectum and sigmoid colon, with the latter invading the small intest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 29 publications
0
17
0
1
Order By: Relevance
“…Out of the 17 cases studied by the authors, none were noted to have GI perforation which was a unique presentation in our patient. A second literature review was performed by Kojima et al in 2021 where the authors reported a total of 28 cases from 1993 to 2019 [ 1 ]. Here, only four cases of RCC demonstrated no metastasis which was also consistent with our patient.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of the 17 cases studied by the authors, none were noted to have GI perforation which was a unique presentation in our patient. A second literature review was performed by Kojima et al in 2021 where the authors reported a total of 28 cases from 1993 to 2019 [ 1 ]. Here, only four cases of RCC demonstrated no metastasis which was also consistent with our patient.…”
Section: Discussionmentioning
confidence: 99%
“…Nonmalignant RCC therefore, appears to be more infrequent than malignant RCC. In the same study, the authors found that the median overall survival of patients with undifferentiated carcinoma with rhabdoid features was three months [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations